Psicologia humanista e ciclo gravídico puerperal : compreensões através de atendimento psicológico online - Tondin, Bruna (2021)
The present study refers to the results of the research developed in the Post-Graduation Program in Psychology of the Universidade Federal de Mato Grosso, Cuiabá campus, articulating the themes of Humanistic Psychology, Pregnancy-Puerperal Cycle and Humanization. The theoretical reference used in Psychology is the Person-Centered Approach (PCA), one of the main currents in Humanistic Psychology, which has as its principle the belief in the tendency of the human being to develop and live harmoniously with its environment. It postulates that in every living organism, there is an inherent flow toward the constructive realization of the maturational development of life. The pregnancy-puerperal cycle is the process of generating a life, which demands physiological, psychological, and social adaptations and changes in the pregnant person's life, and the way she experiences these changes has repercussions on her pregnancy experience. This process is influenced by the previous experiences of those involved, by their belief system, values, education, culture, and also by the existential, welfare, and socioeconomic context in which it occurs. Considering that the experience of pregnancy is a unique and particular moment for each person, we understand that the practice of humanization in the puerperal pregnancy cycle is important, because it is related to respect, welcoming, privacy, safety, and sharing of information with the pregnant woman, and it can facilitate human development. Thus, this study aimed to understand the experiences and feelings of pregnant women associated with the puerperal pregnancy cycle, which may or may not involve humanization, and to contribute to the field of knowledge related to the theme. To this end, psychological care was provided online for pregnant women assisted by the Tijucal Health Center in Cuiabá, MT. The online service was adopted as a possible way to collect information due to the social isolation experienced because of the Covid-19 Pandemic. The method used in the consultations was based on the PCA. With this method we intend to facilitate the pregnant women's freedom of expression and broaden their perceptions about how they live their experiences, maintaining a posture of openness and acceptance based on the facilitating attitudes of PCA - unconditional positive regard, congruence and empathic understanding. The consultations were carried out using information and communication technologies, regulated by Resolutions Nº 11 of May 11, 2018 and Resolution Nº 04 of March 26, 2020 of the Federal Council of Psychology. Two pregnant women between 26 and 29 years old, respectively in the third trimester and second trimester of pregnancy participated in the study. The understanding of the data showed that pregnant women lived remarkable experiences in their lives that influence their relationship with pregnancy. In order to understand the meanings of the experiences associated with the feelings of pregnant women in relation to the puerperal pregnancy cycle, we identified the following cores of meaning: experiences and understandings about the history of the pregnant woman; experiences that permeate the marital relationship; remarkable experiences about the previous experience of childbirth; experiences that cover the (un)humanization of care; experiences about the baby's health; and, experiences that understand the acceptance of pregnancy. The comprehensions of the data showed that the pregnant women lived remarkable experiences in their lives that influenced their relationship with pregnancy, it also showed that the psychological care online made possible a space of shelter and free expression for the pregnant women, that crosses the technological screen and touches the person, their affections and feelings, awakening their potentialities and capacity to (re) organize and conduct their pregnancy-puerperal cycle in a more autonomous and conscious way.